Determinan Kemiskinan: Studi Kasus 10 Kota/Kabupaten di Provinsi Nusa Tenggara Barat Periode 2017-2022 - Pramesti, Muti Dian; Riyardi, Agung (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Poverty is a condition when a person cannot fulfill their basic needs or live a decent life. Poverty basically arises due to many factors such as difficulty finding work, limited capital, low quality of education and other factors. This research aims to study how the GRDP rate, unemployment rate, and human development index affect the poverty rate of 10 cities/districts in West Nusa Tenggara in the period 2017-2022. Secondary data is used in this technique and uses panel data regression to analyze the data. The model selection test results show that the Fixed Effect Model is the best. According to the partial significance test results, the human development index affects the poverty rate at alpha α (0.05). The coefficient of determination (R2) is 0.994, which means that the simultaneous contribution of the independent variable to the dependent variable is 99.4 percent. Other additional variables not included in the model affect the remaining part.